Prescribing Pattern of Antimicrobial Agents in Patients with Pelvic Inflammatory Disease in a Tertiary Care Hospital at Rural Part of Western Nepal - Neupane, Ganesh Prasad; Rai, Maya; Gurung, Sonam; Pandeya, Dipendra Raj (Journal of Nepalgunj Medical College, 2023)
Introduction: Antibiotics are the most frequently prescribed drugs in patients with Pelvic Inflammatory Diseases. Appropriate antibiotic prescriptions in health care institutions are an important element in quality of care, infection management and cost control.Aims: To analyze prescription pattern of antimicrobial agents in patients with pelvic inflammatory diseases.Methods: This quantitative cross-sectional study was conducted including 300 patients' prescriptions, at Karnali Academy of Health Sciences Jumla Nepal for period of six months during August 2021 to January 2022. This study was based on medication utilization form, which was designed on basis of World Health Organization core drug use indicator format.Results: Females were in ages from 12 to 69 years, with mean of 30.46 ± 18.71 years. Chronic Pelvic inflammatory Disease was most prevalent in 20–29 age group (47%) while, lowest in 60–69 age group (1.67%). The total number of prescribed drugs was 796 averaging 2.65 drugs per prescription. The most commonly prescribed antimicrobials were azithromycin (30.15%), tinidazoles (25.25%) and ofloxacin (8.16%). Only 15.5% of drugs were prescribed with generic names and all were from essential list of medicines. 92.8% of prescriptions were administered orally, while 7.8% parenteral. However 76.34% of prescriptions were considered irrational.Conclusion: The high prevalence of irrational prescriptions suggests need for interventions to improve healthcare provider's adherence to established treatment guidelines. Dominance of specific drug classes underscores importance of tailoring treatments to the specific pathogens involved in Pelvic Inflammatory Disease. Suggesting potential room for improvement inadherence to evidence-based guidelines.